Terpenoid Isolation from Baccaurea Lanceolata Muell. Arg Fruit - Kunti Nastiti; Samsul Hadi (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2020)
Fruits of Baccaurealanceolata is commonly used by tribe banjar in south Borneo to protect the skin damages due to sun light. People apply the pulverized fruits to the skin that will be exposed to sunlight. Antioxidant bioassay method (DPPH) is used to prove the effectiveness of the fruits.Baccaurea lanceolata fruitsvwere extracted by 70% ethanol, followed by fractionation with n-hexane, ether, ethyl acetate and methanol to give n-hexane (fr-H), ether (fr. Et2O), ethyl acetate (fr. EtOAc) and methanol (fr. MeOH) fractions respectively. Preparative TLC (SiO2) of the fr. EtOAc that showed the the highest antioxidant activity among those fractions. Based on spectroscopic data and comparison with reported data, the isolated compounds were identified as β-Sitosterol.